Macrotrabecular-massive subtype-based nomogram to predict early recurrence of hepatocellular carcinoma after surgery. Issue 4 (6th April 2023) - Yang, Yong; Mao, Shuqi; Fang, Jiongze; Wang, Gaoqing; Shan, Yuying; Yu, Xi; Lu, Caide
Abstract : Objectives: To analyze the predictive factors on early postoperative recurrence of hepatocellular carcinoma (HCC) and to establish a new nomogram to predict early postoperative recurrence of HCC. Methods: A retrospective analysis of 383 patients who had undergone curative resection between February 2012 and September 2020 in our center was performed. The Kaplan–Meier method was used for survival curve analysis. Univariate and multivariate Cox regression were performed to identify independent risk factors associated with early recurrence, and a nomogram for predicting early recurrence of HCC was established. Results: A total of 152/383 patients developed recurrence after surgery, of which 83 had recurrence within 1 year. Multivariate Cox regression analysis showed that preoperative alpha-fetoprotein level ≥400 ng/ml ( P  = 0.001), tumor diameter ≥5 cm ( P  = 0.009) and MVI ( P  = 0.007 and macrotrabecular-massive HCC ( P  = 0.003) were independent risk factors for early postoperative recurrence of HCC. The macrotrabecular-massive-based nomogram obtained a good C-index (0.74) for predicting early recurrence of HCC, and the area under the curve for predicting early recurrence was 0.767, which was better than the single American Joint Committee on Cancer T stage and Barcelona Clinic Liver Cancer stage. Conclusions: The nomogram based on macrotrabecular-massive HCC can effectively predict early postoperative recurrence of HCC.